Partisipasi pedagang sayur dalam pengelolaan sampah Pasar Tradisional Sanggeng di Kabupaten Manokwari - Oktavian Soter; Soetjipto Moeljono; Yolanda Holle (Cassowary, 2021)
The focus of this research is to examine the participation of traders in market waste management to achieve environmental cleanliness. This is intended so that there is involvement of traders to participate responsibly both actively and passively to achieve environmental cleanliness. This study aims to (1) determine the participation of market vegetable traders in waste management, and (2) analyze the factors that influence the participation of vegetable traders in waste management. The research was conducted at Sanggeng Market as a vegetable trading center in Manokwari Regency. The method used in this research is a survey method with in-depth interview techniques and observation of 52 vegetable traders who trade vegetables at the market of Sanggeng in Manokwari Regency. Data were analyzed using descriptive statistical analysis and inferential statistics. Descriptive statistics used are competency tests and inferential statistics used are Spearman correlation analysis. The results of the study concluded, (1) the participation of vegetable traders shows that they are involved in all stages of waste management, namely the stages of collection, separation, transportation, recycling, and utilization, and (2) there is a correlation between age, education level, acceptance and trading experience.